Immigration Routes From Turkestan To Turkey - Ganiyev Oybekovich; Nishonova Rakhmonberdiyevna (Penerbit Jurnal Indonesia, 2024)
In this article, an attempt was made to comprehensively cover the subject based on the information presented in scientific studies about the reasons for the migration of immigrants who moved from Turkestan to Turkey during the Soviet period, the difficulties they faced along the way, and how they lived as immigrants. This process is not only of historical importance, but even today it plays an important role in strengthening the relations between the Turkic peoples.